Prevalence and severity of physical intimate partner violence during pregnancy among adolescents in eight sub-Saharan Africa countries : A cross-sectional study - Nyemgah, Caroline A.; Ranganathan, Meghna; Nabukalu, Doreen; Stockl, Heidi (PLOS Glob Public Health, 2024)
Globally, intimate partner violence (IPV) is highly prevalent, with adolescents being particularly vulnerable, especially during pregnancy. This study examines the prevalence and severity of physical IPV among pregnant adolescents in sub-Saharan Africa (SSA). We analyzed data from Demographic Health Surveys collected between 2017–2021 from eight SSA countries, involving 2,289 ever-pregnant adolescents aged 15–19. Physical IPV during pregnancy was defined as experiencing physical harm while pregnant by a husband, former partner, current boyfriend, or former boyfriend. Severity of physical IPV included experiences such as kicking, choking, weapon threats, and serious injuries. Logistic regression analysis was conducted, with results presented as unadjusted and adjusted odds ratios with 95% confidence intervals. The prevalence of physical IPV during pregnancy among adolescents in the eight SSA countries ranged from 2.9% to 12.6%, with 5.6% experiencing severe lifetime physical IPV and 6.3% severe physical injuries. We found a strong association between physical IPV during pregnancy and severe lifetime physical IPV (aOR: 6.8, 95% CI: 4.5–10.4) and severe injuries (aOR: 9.2, 95% CI: 6.0–14.2), even after adjusting for covariates. Physical IPV during pregnancy is common among adolescents in SSA and is associated with severe physical lifetime IPV. Addressing this issue in low-resource settings requires collaborative efforts among community stakeholders, health system practitioners, and policymakers to protect vulnerable adolescent girls during pregnancy.